PERSEPSI PESERTA DIDIK TENTANG PENYELENGGARAAN KONSELING KELOMPOK OLEH MAHASISWA PRAKTIK PENGALAMAN LAPANGAN BIMBINGAN KONSELING DI SMP N 12 PADANG - -, Melawati - (Bimbingan dan Konseling, 2014)
This research is motivated by the conditions encountered in the field that the implementation of group counseling Student Counseling Practice Field Experience is not in accordance with what is expected. This study aimed to describe the perceptions of students to: 1) The leader of the group 2) Members of the group and, 3) The benefits of group counseling services. This study is a quantitative descriptive research, the entire study population of learners who have conducted group counseling organized by the students of SMP N 12 PLLBK in Padang as many as 50 people. Samples were taken with a total sampling technique. The instrument used in this study was a questionnaire, while the data used for the analysis of the percentage formula. This research reveals generally be in good enough category. Furthermore, when seen perceptions of group members to the group leader in the category very well. Beyond the perception of the group members to other members in the category quite well and the group members perceptions of the benefits of group counseling services in the category quite well. Based on these results the researchers suggest to students next PPLBK that organizes counseling services with a better group to students in order to achieve the desired objectives and implementation is more effective.